Sustainability Based Financial Risk Management Strategies For Long Term Resilience: A Systematic Review - Rindi Wahyuni; Berliana Febriyanti; Ghina Laila; Deni Sunaryo; Yoga Adiyanto (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study conducted a systematic literature review on the application of sustainability principles in financial risk management in the banking, agriculture, infrastructure, and decentralized technology sectors. By utilizing a sustainability-based approach and early warning metrics, this study identified significant benefits that can strengthen the financial resilience of organizations to long-term uncertainty. The findings show that this approach is not only effective in reducing financial risks but also generates social and environmental benefits, such as improved reputation, public trust, and strengthened stakeholder relationships. However, the implementation of this approach is faced with challenges, including limited resources, low awareness among organizations, and minimal regulations that support the adoption of sustainability in risk management. Recommendations from this study include the development of more supportive regulations, increased investment in predictive technology, and further in-depth research to strengthen the integration of sustainability in financial risk management. These findings are expected to encourage the adoption of a more strategic, responsive, and sustainable risk management approach, which can ultimately improve organizational resilience in the future.